Mesofaunal assemblages in soils of selected crops under diverse cultivation practices in central South Africa, with notes on collembola occurrence and interactions - Badenhorst, Hannelene (University of the Free State, 2016)
Soil is a complex medium, comprised of both biotic and abiotic components. Interactions between these components are responsible for the beneficial services provided within different ecosystems. The biotic component, which is also referred to as the active role players in the soil, is responsible for these services. The incidence of these organisms is influenced by the abiotic factors, which act as filtering mechanisms that select for certain species to occur within certain areas. Considering an ever-increasing human population, these services could prove beneficial, since it could improve crop yields at minimal cost without exploiting the soil resource. Many farmers are now changing their farming methods to more sustainable and conservation focused practices to try and reduce the disruption of soil community structures and to optimize the complexity and resilience of these communities. Disturbances lower the complexity of soil communities and therefore limit the services that could be provided. This study focused on the fluctuations in diversity of selected role players within the soil medium due to the presence of certain agricultural practices and environmental changes. Sampling for this project was conducted at six localities in the Free State Province between 2011 and 2014. Three of the localities are located in the Nama Karoo Biome and the other three in the Grassland Biome. The farms Vaaldam, Koppieskraal, Thornberry and Klein Brittanje were selected due to the diversity of agricultural practices and management strategies applied. The rest of the localities were the Paradys Experimental Farm, which is the experimental farm of the University of the Free State, where a pesticide trial was conducted and the farm Eureka, which was exposed to pollutants from a goldmine tailings dam. The variation in events and the general environment posed the perfect opportunity to observe and evaluate fluctuations in the diversity of the selected faunal groups within the relevant soils. Sampling was conducted in the porosphere of each plant. All the plants selected for sampling were in optimal condition and away from the edges of the field. Samples were marked and transported to the lab where the organisms were extracted by means of the Berlese-Tullgren funnel extraction method. Sorting and identification were subsequently completed from which a reference collection was compiled and stored in ethanol. Fluctuations in the diversity of the selected fauna was observed throughout this study. Agricultural practices had a definite influence on the severity of these fluctuations. Mechanical and chemical disturbances usually had a reduction effect on the diversity at first, which was followed by an increase in the abundance of certain opportunistic species. In some cases, these increases were quite severe, since certain species would flourish in the absence of competition and predator pressure, especially in the case of introduced species. Incorporation of stubble into the soil should be carefully managed, as this could create problems such as compaction. In spite of a certain degree of compaction, it was still found that soils with a higher organic component were more resilient in the presence of disturbances. Stubble-burning influenced the vertical distribution of soil mesofauna due to the condensation effect of such an event. The influence of chemicals depend on the persistence of the chemical used, as well as the complexity of the community before exposure. In already compromised areas, the effect of chemicals were far more detrimental to the community structure than at a natural site where a single application was done. The effect of pollutants from a tailings dam reduced the diversity considerably and only a few species were present at these sites. For species to occur within this heavy metal polluted area, they must be able to either tolerate or avoid the pollutants. It was clear that each locality with its specific influencing factors selected for certain species to be present. Fields that were minimally disturbed and where organic materials were incorporated into, the soils had a higher tolerance to disturbances. This was due to a more complex community structure within the soil, thus indicating that even in the presence of a disturbance, these soils could still provide services.

Grond is ‘n komplekse medium wat uit beide biotiese en abiotiese komponente saamgestel is. Inteaksies tussen hierdie komponente is verantwoordelik vir die voordelige dienste wat in verskillende ekostelsels verskaf word. Die biotiese komponent, wat ook na verwys word as die aktiewe rolspelers in die grond, is verantwoordelik vir hierdie dienste. Die voorkoms van hierdie organismes word beïnvloed deur die abiotiese faktore wat dien as filtreeringsmeganismes wat verantwoordelik is vir die voorkoms van sekere spesies in sekere gebiede. Met verwysing na die groeiende menslike bevolking kan hierdie dienste as voordeel aangewend word omdat dit obrengste kan verhoog met minimale insetkostes, sonder om die grond uit te buit. Baie boere is in die proses om hul boerdery metodes te verander na ‘n meer volhoubare sisteem, met bewaring as uitgangspunt deurdat die versteuring in gondstrukture geminimaliseer word om optimale kompleksiteit en weerstand van grondgemeenskappe te verseker. Versteurings verlaag die kompleksiteit van grondgemeenskappe wat tot gevolg het dat die dienste wat hierdie gemeenskappe bied ingekort word. Hierdie studie fokus op die fluktuasies in diversiteit van geselekteerde rolspelers binne die grondmedium aan die hand van die teenwoordigheid van sekere landboupraktyke en omgewingsveranderlikes. Grondmonsters vir hierdie projek was by ses lokaliteite in die Vrystaat tussen 2011 en 2014 versamel. Drie van hierdie lokaliteite is in die Nama-Karoo Bioom en die ander drie is in die Grasveld Bioom. Die plase Vaaldam, Koppieskraal, Thornberry en Klein Brittanje was geselekteer weens die diverse landboupraktyke en bestuursstrategieë wat daar gevolg is. Die ander lokaliteite was die Paradys Proefplaas van die Universiteit van die Vrystaat, waar ‘n proef met plaagdoders uitgevoer is en die plaas Eureka wat aan besoedeling van ‘n naby geleë goudmynslikdam blootgestel was. Die variasie in grondbestuurpraktyke en die algemene omgewing het die ideale geleentheid verskaf om diversiteitsfluktuasies van geselekteerde faunistiese groepe in verskillende gronde waar te neem en te evalueer. Al die grondmonsters was in die porosfeer van die plante geneem. Al die plante wat vir monsterneming geselekteer is, was in ‘n optimale toestand, en verwyder van die rante van die landerye. Die monsters was gemerk en tot by die laboratorium vervoer waar die organismes deur middel van die Berlese-Tullgren ekstraksie metode geekstraheer is. Sortering en identifisering was uitgevoer en ‘n verwyssingsversameling is saamgestel en in etanol gestoor. Fluktuasies in die diversiteit van die geselekteerde fauna is reg deur die studie waargeneem. Landboupraktyke het ‘n defnitiewe invloed op die intensiteit van hierdie fluktuasies gehad. Meganiese en chemiese versteurings het gewoonlik ‘n aanvanlike afname in diversiteit getoon, gevolg deur ‘n toename. In sommige gevalle was hierdie toenames baie opvallend omdat sommige spesies floreer het in die afwesigheid van kompetisie en predatoriese druk, veral in die geval van indringer spesies. Die inkorporering van plantmateriaal in die grond moet baie omsigtig bestuur word omdat dit probleme, soos kompaksie, kan veroorsaak. Ten spyte van ‘n mate van kompaksie is daar tog gevind dat grond met ‘n hoër organiese samestelling meer weerstand teen verandering bied. Die brand van plantmateriaal in die lande het die vertikale verspreiding van grondmesofauna as gevolg van die kondensasie faktor beïnvloed. Die invloed van chemikalië word deur die volharding van die spesifieke chemikalië, asook die kompleksiteit van die grondgemeenskap voor bloodstellig bepaal. In gebiede wat reeds versteur was, het die effek van chemikalië ‘n groter invloed getoon as in die natuurlike veld waar slegs ‘n enkele bespuiting toegedien is. Die effek van besoedeling van ‘n slikdam het die diversiteit aansienlik verminder en slegs ‘n paar spesies was teenwoordig in die besoedelde gebiede. Hierdie spesies kon moontlik hier voorgekom het weens hul vermoë om swaarmetaalvergiftiging te vermy of te verdra. Dit was diuidelik dat elke lokaliteit met sy spesifieke omstandighede selekteer vir die teenwoordigheid van sekere spesies. Landerye wat minimaal ontwrig was en waar organiese materiaal in die grond ingewerk was, het ‘n hoër toleransie vir versteuring getoon. Dit was as gevolg van ‘n meer komplekse gemeenskapstruktuur in hierdie grond wat tot gevolg gehad het dat selfs in die teenwoordigheid van versteurings, hierdie grond steeds ekostelsel dienste kon bied.
Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2016
Keywords: Soil mesofauna diversity; Tillage; Stubble-burning; Biocide application; Pollution; Faunal preferences; Collembola